Gender-Specific Hippocampal Dysrhythmia and Aberrant Hippocampal and Cortical Excitability in the APPswePS1dE9 Model of Alzheimer's Disease. (20th October 2016) - Papazoglou, Anna; Soos, Julien; Lundt, Andreas; Wormuth, Carola; Ginde, Varun Raj; Müller, Ralf; Henseler, Christina; Broich, Karl; Xie, Kan; Ehninger, Dan; Haenisch, Britta; Weiergräber, Marco
Abstract : Alzheimer's disease (AD) is a multifactorial disorder leading to progressive memory loss and eventually death. In this study an APPswePS1dE9 AD mouse model has been analyzed using implantable video-EEG radiotelemetry to perform long-term EEG recordings from the primary motor cortex M1 and the hippocampal CA1 region in both genders. Besides motor activity, EEG recordings were analyzed for electroencephalographic seizure activity and frequency characteristics using a Fast Fourier Transformation (FFT) based approach. Automatic seizure detection revealed severe electroencephalographic seizure activity in both M1 and CA1 deflection in APPswePS1dE9 mice with gender-specific characteristics. Frequency analysis of both surface and deep EEG recordings elicited complex age, gender, and activity dependent alterations in the theta and gamma range. Females displayed an antithetic decrease in theta ( θ ) and increase in gamma ( γ ) power at 18-19 weeks of age whereas related changes in males occurred earlier at 14 weeks of age. In females, theta ( θ ) and gamma ( γ ) power alterations predominated in the inactive state suggesting a reduction in atropine-sensitive type II theta in APPswePS1dE9 animals. Gender-specific central dysrhythmia and network alterations in APPswePS1dE9 point to a functional role in behavioral and cognitive deficits and might serve as early biomarkers for AD in the future.